2016
DOI: 10.1016/j.chemosphere.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and speciation of arsenic in New England seaweed species harvested for food and agriculture

Abstract: A survey of arsenic (As) concentrations and speciation was conducted on 10 species of seaweed from commercial harvesters and from collection at two sites in New England. Concentrations of As ranged from 4–106 mg/kg, mostly in the form of arsenosugars, with the distribution of arsenosugar analogs varying between taxa. In brown algae, As levels were correlated with phosphate concentrations, and arsenosugar speciation reflected differences in sulfur and phosphate concentrations between taxa. Several samples of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 60 publications
11
42
1
Order By: Relevance
“…Recent investigations by the University of Dartmouth concluded that iAS is also present in food products (rice, beer, wine, chicken, etc.) [Taylor and Jackson, ]. We observed a continuously increasing concentration–response of γH2AX with the three arsenic compounds tested, reflecting overall genotoxicity that may be caused by oxidative stress and altered patterns of DNA repair [Martinez et al, ; Faita et al, ].…”
Section: Discussionmentioning
confidence: 79%
“…Recent investigations by the University of Dartmouth concluded that iAS is also present in food products (rice, beer, wine, chicken, etc.) [Taylor and Jackson, ]. We observed a continuously increasing concentration–response of γH2AX with the three arsenic compounds tested, reflecting overall genotoxicity that may be caused by oxidative stress and altered patterns of DNA repair [Martinez et al, ; Faita et al, ].…”
Section: Discussionmentioning
confidence: 79%
“…The speciation of arsenic in filtered water samples was determined at the Trace Element Analysis laboratory at Dartmouth College on an Agilent LC1120 liquid chromatograph, using an anion‐exchange column (Hamilton PRP‐X100), coupled to an Agilent 8900 triple quadrupole ICP‐MS (Taylor and Jackson ). The eluent was 20 mM (NH 4 ) 2 CO 3 at a flow rate of 1.1 mL min −1 with a column temperature of 35°C.…”
Section: Methodsmentioning
confidence: 99%
“…Seaweeds produced for consumption have continued to attract attention. A survey of As concentrations and speciation was conducted on 10 species of seaweed from commercial harvesters and from collection at two sites in New England, USA 69 . Samples were extracted using HNO 3 and microwave digestion prior to determination of the As species by ICP-MS (total As) and…”
Section: Montezuma Well Through Vents In the Bottom Of This Collapsedmentioning
confidence: 99%